2009
DOI: 10.1186/1479-5868-6-50
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intensity, prevalence and duration of everyday activities in Swiss school children: a cross-sectional analysis of accelerometer and diary data

Abstract: Background: Appropriately measuring habitual physical activity (PA) in children is a major challenge. Questionnaires and accelerometers are the most widely used instruments but both have well-known limitations. The aims of this study were to determine activity type/mode and to quantify intensity and duration of children's everyday PA by combining information of a time activity diary with accelerometer measurements and to assess differences by gender and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 25 publications
(31 reference statements)
5
64
1
6
Order By: Relevance
“…This contrasts with earlier reports of declining levels of HPA for the majority of youth over a 5-year period of growth from childhood to adolescence, regardless of sex or weight status [26] and the trend of decreasing activity levels of children and youth in general [27]. It is possible that monitoring a patient's activity level while participating in a study may be a sufficient stimulus to effectively maintain what would otherwise be a predictable pattern of decreasing activity level with age [28]. This highlights a valuable opportunity to have a positive impact on lung function decline, by promoting a physically active lifestyle throughout childhood, to encourage the maintenance of activity and enhance the carry-over into adulthood [29].…”
Section: Discussionmentioning
confidence: 75%
“…This contrasts with earlier reports of declining levels of HPA for the majority of youth over a 5-year period of growth from childhood to adolescence, regardless of sex or weight status [26] and the trend of decreasing activity levels of children and youth in general [27]. It is possible that monitoring a patient's activity level while participating in a study may be a sufficient stimulus to effectively maintain what would otherwise be a predictable pattern of decreasing activity level with age [28]. This highlights a valuable opportunity to have a positive impact on lung function decline, by promoting a physically active lifestyle throughout childhood, to encourage the maintenance of activity and enhance the carry-over into adulthood [29].…”
Section: Discussionmentioning
confidence: 75%
“…Este instrumento ha tenido un uso relativamente reducido en la población pediátrica, por limitada cooperación en el proceso y confiabilidad puesta en duda, aun con adolescentes. Esto ha cambiado, y según estudios recientes, comparando el diario de actividad con acelerometría en niños o adolescentes, la validez de este instrumento fue calificada de razonable y moderada (19)(20)(21). Otras publicaciones han mostrado que los diarios de actividad pueden aplicarse en estudios con un número importante de sujetos, más de 300 en el trabajo de Pfitzner et al (22) en Alemania y 400 en el de Pearce et al (23) en Inglaterra.…”
Section: Nivel De Intensidad De Las Principales Actividades Físicas Dunclassified
“…La realidad parece intermediaria; si la validación del diario de actividad no fue tema del presente estudio, es un hecho que no ha sido bien establecida por otros. Algunos trabajos calificaron la validez del diario de actividad como moderada o razonable, aportando cifras o valores de correlación con acelerometria que no sobrepasan un r = 0,58 (20,21,26,28). Sin embargo, en 403 adolescentes portugueses, Machado-Rodrigues et al (19), compararon las cpm con el gasto energético de las actividades registradas por el diario y reportaron una asociación RHO de 0,65 en varones y 0,69 en mujeres.…”
Section: Figuraunclassified
See 1 more Smart Citation
“…In a recent review article (12) on accelerometerdetermined physical activity data in children, only four studies (13)(14)(15)(16)) with a longitudinal design were identified. All except one (14)(15)(16) reported on significant lower activity pattern during winter.…”
mentioning
confidence: 99%